The The Role of Tongue Twister to Improve the Students’ Speaking Skill - Yuniar, Yuni; Pahlevi, Muhammad Reza; Hoerniasih, Nia (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2021)
Recently the ability to English speaking is very necessary since English has become a foreign language in Indonesia. A correct speech is become crucial to avoid misunderstanding conveying the information to the listener. Therefore, teaching English speaking is very necessary to the teacher in improving the students’ speaking skills. The main reason why learning to speak English is very difficult for the students is because students often use the Indonesian language (mother tongue) as the main language and are not accustomed to speaking in English in their daily life. One of the alternatives technique that can be used by the teacher is using tongue twister. The aims of this study is to explore about what are the problems that faced by the students while learning English speaking in Tongue Twister assisted. The classroom action research is a method that conducted in this research. There are two Cycles in this research and both of cycles showed of 77.14% of students has obtained a score of 75 and 77.13%. This result shows that the students have met the success criteria of the research and the students actively participate in the teaching and learning processes during English-speaking class.